2016
DOI: 10.3109/10826084.2016.1155607
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anonymity in Determining the Self-Reported Use of Cocaine and Nonmedical Prescription Stimulant Use Among College Students

Abstract: These results suggest that NPSU may not have the same perceived negative social consequences as other more stigmatized stimulant drugs, with young men in particular giving little weight to the potential consequences of NPSU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The study was cross-sectional and hence the direction of causality of any effects cannot be established – this would require longitudinal designs. There are limitations inherent in the study design – diagnostic assessment may be less accurate (more “noisy”) via such an online survey compared to in-person assessment by a clinician; there may be responder biases; and there may be under-reporting (though this possibility is mitigated by virtue of the survey being anonymous) (for an analysis of the complex relationship between anonymity and reporting stimulant use, please see Zander et al, 2016). Additionally, self-report questions pertaining to substance use have their own limitations: for example, individuals may not disclose the full extent of their use or may not report it accurately due to bias.…”
Section: Discussionmentioning
confidence: 99%
“…The study was cross-sectional and hence the direction of causality of any effects cannot be established – this would require longitudinal designs. There are limitations inherent in the study design – diagnostic assessment may be less accurate (more “noisy”) via such an online survey compared to in-person assessment by a clinician; there may be responder biases; and there may be under-reporting (though this possibility is mitigated by virtue of the survey being anonymous) (for an analysis of the complex relationship between anonymity and reporting stimulant use, please see Zander et al, 2016). Additionally, self-report questions pertaining to substance use have their own limitations: for example, individuals may not disclose the full extent of their use or may not report it accurately due to bias.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that students do not hold strong negative perceptions related to cannabinoids, which are in contrast with use other more stigmatized drugs. This is also illustrated by the finding [15] that male participants are more likely to report nonmedical prescription stimulant compared to other illicit stimulant drug use.…”
Section: Sample Characteristicsmentioning
confidence: 93%
“…Extensive research has observed the detrimental role of NMUPS in damaging college students' academic performance [4] and more alarmingly, students' short-term and long-term health [5][6][7]. Despite control and regulation, college students' NMUPS activities have been on the rise [8][9][10].…”
Section: Introductionmentioning
confidence: 99%